The rewarding and cognitive effects of corticosterone in mice - Ebada, Mohamed Elsaed Elsayed (2012)
Corticosterone is the main glucocorticoid in rodents. Its secretion follows a circadian rhythm and is increased in response to stress. Corticosterone is thought to possess rewarding effects. For example, enhanced corticosterone secretion is associated with the exposure to natural rewards such as food, sex and running, and it has been reported that corticosterone is implicated in drug-seeking behaviour. In addition, rats orally self-administer the steroid hormone and are motivated to nose-poke for stress-like levels of corticosterone, suggesting that the stress hormone has rewarding effects on its own, although this proposal is not supported by conditioned place preference studies. Corticosterone is also found to be critical for learning and memory performance, but it is unclear whether cognitive effects of the hormone are modulated by its rewarding properties. Elevated glucocorticoid levels have been reported to accompany certain psychiatric and cognitive disorders, but it is not clear whether this is an underlying cause or a consequence of these diseases.